A new species of the rodent genus Necromys Ameghino (Cricetidae: Sigmodontinae: Akodontini) from the Chaco Serrano grasslands of northwestern Argentina - Jayat, Jorge Pablo (2016)
In this study we name and describe a new species of the genus Necromys from northwestern Argentina based on genetic (mtDNA of 77 specimens) and morphologic (assessment of 122 specimens) evidence. Results indicate that the new form is sister species to N. amoenus and highly divergent genetically from all other species of Necromys (≥11.6% divergent). Similarly, the new species presents several unique morphological differences (in skin and skull characters) compared with all other species of the genus and is morphometrically distinct compared with four Argentine taxa. Finally, we assess the lectotype of Necromys conifer, discuss its morphologic similarities with other species of the genus, and argue for maintenance of the generic epithet Necromys. The description of this new species highlights, once again, the continuing need for collecting small mammals and conducting collections-based research.